Ligand Engineering Achieves Suppression of Temperature Quenching in Pure Green Perovskite Nanocrystals for Efficient and Thermostable Electroluminescence - Kaiwang Chen; Qing Du; Qiufen Cao; Chao Du; Shangwei Feng; Yutong Pan; Yue Liang; Lei Wang; Jiangshan Chen; Dongge Ma (Nano-Micro Letters)
Highlights The innovative synthesis of pure green FAPbBr3 nanocrystals at room temperature was exploited by employing aromatic amine ligands to refine the perovskite nanocrystals with high quality and excellent optoelectronic properties. The proposed ligand engineering strategy firstly realized the suppression of emission thermal quenching effect in the organic-inorganic hybrid FAPbBr3 nanocrystals. It was demonstrated that the FAPbBr3 based light-emitting diodes achieved a room temperature external quantum efficiency (EQE) of 21.9% at the luminance of 1580 cd m-2, and only presented less than 10% loss in EQE at a higher temperature of 343 K.